Perancangan Pop Up Book Asma’ul Husna Dengan Teknik Lift The Flap Sebagai Media Pengenalan Pada Murid Paud - reza, ivanda; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
Asma'ul Husna are the names and attributes of Allah SWT. Asma'ul Husna is also the science of Islamic teachings of Tawheed. By studying Asma'ul Husna for a Muslim can get closer to Allah SWT, the Creator. In Asma'ul Husna's learning is usually only a vocal or singing Asma'ul Husna pronunciation. This makes the researchers want to create new learning media Asma'ul Husna. The research was conducted by using qualitative research method that is by conducting interview, observation, documentation, and literature study to get the data used as supporting the design concept of pop up book design of Asma'ul Husna. The results of this design is for the learning media on the target audience. The design of new learning media Asma'ul Husna is to introduce Asma'ul Husna on target audience. Keywords: Design, Pop Up Book, Asma'ul Husna, Aware